2017
DOI: 10.18632/oncotarget.19926
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial genome variation and prostate cancer: a review of the mutational landscape and application to clinical management

Abstract: Prostate cancer is a genetic disease. While next generation sequencing has allowed for the emergence of molecular taxonomy, classification is restricted to the nuclear genome. Mutations within the maternally inherited mitochondrial genome are known to impact cancer pathogenesis, as a result of disturbances in energy metabolism and apoptosis. With a higher mutation rate, limited repair and increased copy number compared to the nuclear genome, the clinical relevance of mitochondrial DNA (mtDNA) variation require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 102 publications
1
26
0
Order By: Relevance
“…As a consequence, combined OXPHOS complex deficiencies would be expected, as observed in 5 cases in our study. According to a recent review, 749 mtDNA mutations have been described for prostate cancer [ 34 ]. Only 80 of these were found in two or more patients, 15 of which are potentially pathogenic according to commonly used prediction tools [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, combined OXPHOS complex deficiencies would be expected, as observed in 5 cases in our study. According to a recent review, 749 mtDNA mutations have been described for prostate cancer [ 34 ]. Only 80 of these were found in two or more patients, 15 of which are potentially pathogenic according to commonly used prediction tools [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent review, 749 mtDNA mutations have been described for prostate cancer [ 34 ]. Only 80 of these were found in two or more patients, 15 of which are potentially pathogenic according to commonly used prediction tools [ 34 ]. We are not aware of any previous study correlating nuclear OXPHOS subunit gene alterations to the frequency of OXPHOS deficiency in prostate carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…AA prostate cancer is more aggressive, takes less time to relapse, shows molecular differences, and has greater likelihood of metastasis than CA prostate cancer (2)(3)(4)(5)(6)(7)(8). Although the molecular mechanisms driving acquisition of these characteristics in AA prostate cancer remain largely unknown, we and others have demonstrated that mitochondrial dysfunction is a key contributing factor to therapeutic resistance (9)(10)(11)(12). One of the reasons for greater prostate cancer aggressiveness in AA men is the existence of defective oxidative phosphorylation (OXPHOS) system in AA prostate cancer cells and tumors (9,12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Although the molecular mechanisms driving acquisition of these characteristics in AA prostate cancer remain largely unknown, we and others have demonstrated that mitochondrial dysfunction is a key contributing factor to therapeutic resistance (9)(10)(11)(12). One of the reasons for greater prostate cancer aggressiveness in AA men is the existence of defective oxidative phosphorylation (OXPHOS) system in AA prostate cancer cells and tumors (9,12,13). We reported that mitochondrial DNA (mtDNA) copy number is reduced in nontumor prostatic tissues in AA men with prostate cancer compared with CA men with prostate cancer (11).…”
Section: Introductionmentioning
confidence: 99%
“…One possibility for how to overcome this dilemma and better characterize the cancerous lesions is mitochondrial DNA (mtDNA). Mitochondrial DNA (mtDNA) mutations are found in various cancer types [65][66][67][68]. Occurrences are found in every cell stage and a high number of copies are discovered in tumors, suggesting a less tight control and common mutations [69].…”
Section: Epithelial Mesenchymal Transition In Endometrial Cancersmentioning
confidence: 99%